ANALISIS PENGARUH RASIO KEUANGAN DAN UKURAN PERUSAHAAN TERHADAP RETURN SAHAM PADA PERUSAHAAN JASA KONSTRUKSI DI BURSA EFEK INDONESIA (Jurnal Tepak Manajemen Bisnis, 2014)
The objectives of This research are to analyze the effect of liquidity, solvability, profitability, activity,capital market and firm size ratio to stock return in construction company. This research also try to answervariable which have powerfull effect to stock return.Population of this study is all off company which listed in Indonesian Capital Market. Sample frameapplied in this research for construction company. Total sample of this research is thirty comany for 2009 to 2011period. Normality, multikolinearity, autocorrelation, heterdekedacity applied for this research as test of dataquality and multiple lenear regression used as tool for test the relationship of independen variables to dependentvariable. T test and F test uses to get the result of partial and simultaneously test.The result of test showed that current ratio, NPM, ROA, Inventory Turn Over, EPS have significant effetto stock return, mean while Long Term Debt to Total Asset, PER and Frm size dont show significant effet to stockreturn. Adjust R Square of this research is 23,9% which mean all of variable which purpose just explain 23,9%variance of dependent variable meanwhile 72,1% explain by the other variables.Keyword :Liquidity, Solvability, Profitability, activity, capital market and firm size